Review of the genus Isolia Förster (Platygastroidea: Platygastridae: Sceliotrachelinae) with description of two new species from India - Kamalanathan, Veenakumari; Buhl, Peter Neerup; Mohanraj, Prashanth (Zootaxa, 2019)
Two new species of Isolia Förster viz. I. bhima Veenakumari and Buhl sp. n. and I. bandoola Veenakumari and Buhl sp.n. are described and illustrated from India. The generic concept of Isolia has been expanded with additional characters. Supplementary characters have been provided to the original descriptions wherever required. All species (except I. longistriata Alekseev), including the six Palearctic species (I. biroi Szabó, I. dobrogica Popovici & Buhl, I. foersteri Szabó, I. hispanica Buhl, I. mongolica (Kozlov) and I. santosi García & Pujade-Villar) and the two Oriental species (I. indica Buhl and I. kalingae Veenakumari & Buhl) have been imaged. Isolia striatitergitis Szabó is transferred to the genus Fidiobia Ashmead, and the images are provided. Isolia kalingae is treated as a junior synonym of I. indica. A key is furnished to differentiate genera in the Isolia-cluster and the species of Isolia treated here.